Przedsiębiorczość personalistyczna – aspekt dydaktyczny - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2014)
This article presents a reflection on the education of business leaders. The analy-sis was based on the phenomenological tradition. The phenomenological ap-proach to teaching is a help in revealing the horizons of individuals – persons, not filling them up, e.g. empowering them. These teaching aids should include certain patterns – for the development of a person, not degradation. Unfortunate-ly, training of business leaders is still based on instrumental rationality: academ-ic teaching is more focused on the transfer of knowledge and less on developing the creativity of students. The phenomenological approach postulates that teach-ing should be more focused on fostering creativity. Two stages are important in the teaching process: cognitive and creative. The first step is to explore pre-existing knowledge, the second triggers the creative potential of the student. The ‘3i’ formula is a method which allows for the combination of both steps and the formation of a creative reality.